THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEES OF SURYA MANDIRI MUHAMADIYAH SURYA MANDIRI COOPERATION IN LHOKSEUMAWE - Yulmaida, Titi; Alisa, Alisa; Ananta, Raisya; Zamharira Alisya, Putria; Nur Ilham, Rico (RADJA PUBLIKA, 2023)
Sharia cooperatives have two backgrounds of establishment and activities that are almost as strong, namely as microfinance institutions and as Islamic financial institutions. Judging from the principles that exist in cooperatives, there is nothing that conflicts with Islamic law. This institution is in accordance with Islamic values. However, it is necessary to improve and monitor the cooperative system, namely, to avoid Riba, Maysir, Ghoror, Batil. Islamic cooperatives do not have a striking system difference with conventional cooperatives. Therefore, the legal umbrella used by sharia cooperatives generally uses the legal umbrella for conventional cooperatives, namely Law No. 25 of 1992 concerning cooperatives. This research is a type of qualitative descriptive research and in collecting data using observation interviews and documentation methods, there are data analysis techniques used, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Muhammadiyah Surya Mandiri Syariah Cooperative helps the Lhoksuemawe community in making savings and loans.